A Comparative Study of the Effect of Chlorhexidine Gel and Hyaluronic Acid Gel on Post-Operative Complications Following Mandibular Third Molars Surgery (Journal of Hama University, 2020)
This clinical study was carried at oral and maxillofacial surgery department at Hama University. This study included random sample of 40 cases of impacted lower third molars. The ages of patients were between 18-25 years. The aime of this study was to compare between Hyaluronic acid and Chlorheixidine 0.2% on pain, edema, trismus and osteitis after impacted lower third molars surgery.The sample was divided into two groups:First group: 20 impacted lower third molars was surgically extracted. Hyaluronic acid was applied in alveolar cavity with surgical suture.Second group: : 20 impacted lower third molars was surgically extracted. Chlorheixidine 0.2% was applied in alveolar cavity with surgical suture.The study showed that both of Hyaluronic acid and Chlorhexidine 0.2% have a positive effect on controlling pain, edema, trismus and osteitis after surgical extraction, with preference for Hyaluronic over Chlorhexidine 0.2% with statistically significant.